2021
DOI: 10.1016/j.clgc.2021.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing Localized Prostate Cancer: Validation of a Combined Clinical Cell-cycle Risk (CCR) Score Threshold for Prognosticating Benefit From Multimodality Therapy

Abstract: Using a retrospective, multi-institutional cohort of men with prostate cancer (N [ 718), this study evaluated a score that combines a genome expression classifier and clinical information to prognosticate progression to metastatic disease in various treatment contexts. A score threshold identified men with intermediate-and high-risk prostate cancer who could safely forgo multimodal therapy. Introduction: The combined clinical cell-cycle risk (CCR) score is a validated model that combines the cell-cycle progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…To address this critical need, we quantified how adding ADT to RT reduces the risk of metastasis in individual patients by applying the metaanalysis results 32 to personalized risk estimates derived from the CCR score, which combines molecular and clinical prognostic information. [22][23][24][25][26]29,30,[33][34][35] The results of the current study revealed that the CCR score can inform personalized ARR because of treatment with ADT, with a substantially reduced 10-year risk of metastasis predicted in those above the Prolaris MMT threshold. This methodology can be applied to any validated nomogram or biomarker that produces an individual risk estimate for metastasis.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…To address this critical need, we quantified how adding ADT to RT reduces the risk of metastasis in individual patients by applying the metaanalysis results 32 to personalized risk estimates derived from the CCR score, which combines molecular and clinical prognostic information. [22][23][24][25][26]29,30,[33][34][35] The results of the current study revealed that the CCR score can inform personalized ARR because of treatment with ADT, with a substantially reduced 10-year risk of metastasis predicted in those above the Prolaris MMT threshold. This methodology can be applied to any validated nomogram or biomarker that produces an individual risk estimate for metastasis.…”
Section: Discussionmentioning
confidence: 64%
“…The RT-alone cohort included 467 patients from two previously described and published, retrospective cohorts who were treated with RT alone as a single modality. 25,26 The clinical cohort included 56,485 patients who underwent a clinical Prolaris biopsy test between January 1, 2020, and October 31, 2022. These patients were untreated at the time of biopsy used for testing, and their clinical follow-up, including treatment choices, is unknown.…”
Section: Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel commercially available clinical-genomic tests four kallikrein panel algorithm (4Kpanel), Oncotype DX, Prolaris, and Decipher can also aid decision making for clinicians. For example, these tests have been shown to reclassify men with NCCN low-risk PCa at greater risk for development of metastatic disease (24,25), identify men with NCCN high-risk PCa who may be candidates for active surveillance (26), and increase confidence for community providers to recommend active surveillance (27). In the future it is possible these tests may help personalize biopsy decisions for many patients.…”
Section: Discussionmentioning
confidence: 99%
“…Swanson et al published [68] a study of 360 men in 2021 using sample tissue from radical prostatectomy specimens, in which CCR was demonstrated to be an independent predictor of metastatic disease and disease-specific mortality after RP (HR = 3.03 [95% confidence interval (CI): 1.49, 6.20]; p = 0.003) and disease-specific mortality (HR = 3.40 [95% CI: 1.52, 7.59]; p = 0.004), respectively. Tward et al addressed the potential benefits of using CCR to determine the need for adjuvant therapy in a study published in 2021 [69]. They used the CCR score and defined a multimodality therapy threshold for patients who had radiotherapy or surgery to assess the need for ADT or radiation, respectively.…”
Section: Which Tests Are Available To Predict Metastatic Disease? Wha...mentioning
confidence: 99%